Предмет: Алгебра,
автор: moksinrostislav
5(m + n)^2 -10 mn
представьте в виде многочлена
Ответы
Автор ответа:
2
5(m+n)^2 - 10mn = 5( (m+n)^2 - 2mn) =
5(m^2 + 2mn + n^2 - 2mn) =5(m^2 + n^2)
5(m^2 + 2mn + n^2 - 2mn) =5(m^2 + n^2)
Автор ответа:
0
Ответ:
5m^2+5n^2
Объяснение:
5(m+n)^2-10mn
5(m^2+2mn+n^2) - 10mn
5m^2+10mn+5n^2-10mn
5m^2+5n^2
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: bakhodir93
Предмет: Русский язык,
автор: valeron2
Предмет: Русский язык,
автор: milana3841